Randomized Controlled Trial Comparing Autologous Protein Solution to Hyaluronic Acid Plus Triamcinolone for Treating Hip Osteoarthritis in Dogs - Franklin, Samuel P.; Franklin, Ashley L. (Frontiers in Veterinary Science, 2021)
Twenty-three dogs with bilateral hip osteoarthritis were used to compare the efficacy of intra-articular injections of autologous protein solution (APS) to hyaluronic acid plus triamcinolone (HAT). Prior to treatment, owner assessments of pain and mobility were obtained using the canine brief pain inventory (CBPI) and Liverpool Osteoarthritis for Dogs (LOAD) questionnaires. Owners were also asked to list all medications used to control signs of pain associated with hip osteoarthritis (OA). In addition, objective kinetic data using a pressure sensitive walkway was used to quantify the relative weight bearing of each of the limbs (total pressure index; TPI). One hip was then selected using a random number generator for injection with HAT and the contralateral hip was injected with APS under the same sedation event. At 1-, 3-, and 6 months following injection, medication usage was recorded and dogs were re-assessed using the CBPI and LOAD questionnaires and using objective gait analysis to determine the TPI. Twenty dogs completed all aspects of the study and statistically significant (p < 0.05) improvements were noted by dog owners at every post-treatment time point in every category of pain and mobility as assessed by the CBPI and LOAD questionnaires. Only 5 dogs, compared to 14 pre-treatment, received any oral NSAID or other analgesic for the duration of the 6-month study period. The TPI, and change in TPI from baseline, were not statistically significantly different between the two treatments at any time point. These data suggest clinical efficacy of both APS and HAT, but fail to show superiority of one treatment vs. the other. The inability to detect a statistically significant difference between the two treatments could be attributable to a true lack of a difference, or a type II statistical error.